Whole Genome Sequencing and Newborn Screening - Botkin, Jeffrey R. (Curr Genet Med Rep, 2016)
Clinical applications of next generation sequencing are growing at a tremendous pace. Currently the largest application of genetic testing in medicine occurs with newborn screening through state-mandated public health programs, and there are suggestions that sequencing could become a standard component of newborn care within the next decade. As such, newborn screening may appear to be a logical starting point to explore whole genome and whole exome sequencing on a population level. Yet, there are a number of ethical, social and legal implications about the use of a mandatory public health screening program that create challenges for the use of sequencing technologies in this context. Additionally, at this time we still have limited understanding and strategies for managing genomic data, supporting our conclusion that genome sequencing is not justified within population based public health programs for newborn screening.